Regime of Obstruction How Corporate Power Blocks Energy Democracy - Carroll, William K. (Athabasca University Press, 2021)
Rapidly rising carbon emissions from the intense development of Western Canada's fossil fuels continue to aggravate the global climate emergency and destabilize democratic structures. The urgency of the situation demands not only scholarly understanding, but effective action. Regime of Obstruction aims to make visible the complex connections between corporate power and the extraction and use of carbon energy. Edited by William Carroll, this rigorous collection presents research findings from the first three years of the seven-year, SSHRC-funded partnership, the Corporate Mapping Project. Anchored in sociological and political theory, this comprehensive volume provides hard data and empirical research that traces the power and influence of the fossil fuel industry through economics, politics, media, and higher education. Contributors demonstrate how corporations secure popular consent, and coopt, disorganize, or marginalize dissenting perspectives to position the fossil fuel industry as a national public good. They also investigate the difficult position of Indigenous communities who, while suffering the worst environmental and health impacts from carbon extraction, must fight for their land or participate in fossil capitalism to secure income and jobs. The volume concludes with a look at emergent forms of activism and resistance, spurred by the fact that a just energy transition is still feasible. This book provides essential context to the climate crisis and will transform discussions of energy democracy. Contributions by Laurie Adkin, Angele Alook, Clifford Atleo, Emilia Belliveau-Thompson, John Bermingham, Paul Bowles, Gwendolyn Blue, Shannon Daub, Jessica Dempsey, Emily Eaton, Chuka Ejeckam, Simon Enoch, Nick Graham, Shane Gunster, Mark Hudson, Jouke Huizer, Ian Hussey, Emma Jackson, Michael Lang, James Lawson, Marc Lee, Fiona MacPhail, Alicia Massie, Kevin McCartney, Bob Neubauer, Eric Pineault, Lise Margaux Rajewicz, James Rowe, JP Sapinsky, Karena Shaw, and Zoe Yunker.